Product Type Calibration Estimator with inversely related PSU level auxiliary variable under Two Stage Sampling - Ankur Biswas; Kaustav Aditya; U.C. Sud (Journal of the Indian Society of Agricultural Statistics, 2025)
In survey sampling, auxiliary information is often used to increase the efficiency of estimators of finite population parameters. The Calibration Approach is one of the popular techniques for such purposes. In this current study, product type calibration estimator of the finite population total has been proposed following well-known Calibration Approach for the situations of availability of inversely related auxiliary information at PSU level under two stage sampling design framework. Statistical properties of proposed product type calibration estimator of population total were studied through a simulation study. The simulation results suggest that the proposed product type calibration estimator is performing better than usual Horvitz-Thompson and linear regression estimators of the population total under two stage sampling design.